PENGGUNAAN MODEL PEMBELAJARAN HYPERTEXT DAN HYPERMEDIA DENGAN BLENDED LEARNING TERHADAP HASIL BELAJAR - Susilawati, Samsul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
Hypertext and hypermedia are kinds of media software that interlink of text, image, graphic, video, and audio. The use of hypertext and hypermedia as a method on a blended learning situation make learning activity more interactive. Users can make connection between text, image, audio clips and video clips as a link or hyperlink. Cooperative skills of students in the methods Hypertex and Hypermedia through Blended Learning in social studies integrated together and learning process with the full meaning, because it is not only related to the achievement of the learning material, but students also learn to operate the computer well and social life when discussions group.The use of hypertext and hypermedia is effective to motivate students learning on of social science. It can also effective to enhance students learning achievement on social science.Keywords: Hypertext and hyperlink; blended learning